Altered immune proteome of Staphylococcus aureus under iron‐restricted growth conditions. Issue 16 (9th July 2014) - Stentzel, Sebastian; Vu, Hai Chi; Weyrich, Anna Maria; Jehmlich, Nico; Schmidt, Frank; Salazar, Manuela Gesell; Steil, Leif; Völker, Uwe; Bröker, Barbara M.
<x xml:space="preserve">Abstract</x> Staphylococcus aureus is one of the major causative agents of severe infections, and is responsible for a high burden of morbidity and mortality. Strains of increased virulence have emerged (e.g. USA300) that can infect healthy individuals in the community and are difficult to treat. To add to the knowledge about the pathophysiology of S. aureus, the adaption to iron restriction, an important in vivo stressor, was studied and the corresponding immune response of the human host characterized. Using a combination of 1D and 2D immune proteomics, the human antibody response to the exoproteomes of S. aureus USA300Δspa grown under iron restriction or with excess iron was compared. Human antibody binding to the altered exoproteome under iron restriction showed a 2.7‐ to 6.2‐fold increase in overall signal intensity, and new antibody specificities appeared. Quantification of the secreted bacterial proteins by gel‐free proteomics showed the expected strong increase in level of proteins involved in iron acquisition during iron‐restricted growth compared to iron access. This was accompanied by decreased levels of superantigens and hemolysins. The latter was corroborated by functional peripheral blood mononuclear cell proliferation assays. The present data provide a comprehensive view of S. aureus exoproteome adaptation to iron restriction. Adults have high concentrations of serum antibodies specific for some of the newly induced proteins. We conclude that iron restriction is a common feature of the microenvironment, where S. aureus interacts with the immune system of its human host.